Comparison of Apoptosis and Autophagy in Human Chondrocytes Induced by the T-2 and HT-2 Toxins - Yu, Fang-Fang (Toxins (Basel), 2019)
In this report, we have investigated the apoptosis and autophagy of chondrocytes induced by the T-2 and HT-2 toxins. The viability of chondrocytes was measured by the MTT assay. Malondialdehyde (MDA) and superoxide dismutase (SOD) kits were used to measure the oxidative stress of chondrocytes. The apoptosis of chondrocytes was measured using flow cytometry. Hoechst 33258 and MDC staining agents were introduced to analyze apoptosis and autophagy induction in chondrocytes, respectively. Protein expression of Bax, caspase-9, caspase-3, and Beclin1 was examined by western blotting analysis. The T-2 and HT-2 toxins significantly decreased the viability of chondrocytes in a time-dependent manner. The level of oxidative stress in chondrocytes induced by the T-2 toxin was significantly higher when compared with that of the HT-2 toxin. The apoptosis rate of chondrocytes induced by the T-2 toxin increased from 3.26 ± 1.03%, 18.38 ± 1.28%, 34.5 ± 1.40% to 49.67 ± 5.31%, whereas apoptosis rate of chondrocytes induced by the HT-2 toxin increased from 3.82 ± 1.03%, 11.61 ± 1.27%, 25.72 ± 2.95% to 36.28 ± 2.81% in 48 h incubation time. Hoechst 33258 staining confirmed that apoptosis of chondrocytes induced by the T-2 toxin was significantly higher than that observed when the chondrocytes were incubated with the HT-2 toxin. MDC staining revealed that the autophagy rate of chondrocytes induced by the T-2 toxin increased from 6.38% to 63.02%, whereas this rate induced by the HT-2 toxin changed from 6.08% to 53.33%. The expression levels of apoptosis and autophagy related proteins, Bax, caspase-9, caspase-3, and Beclin1 in chondrocytes induced by the T-2 toxin were significantly higher when compared with those levels induced by the HT-2 toxin.